2012
DOI: 10.1107/s1600536812004771
|View full text |Cite
|
Sign up to set email alerts
|

4,6-Dinitropyrogallol

Abstract: In the title molecule, C6H4N2O7, the two nitro groups are tilted with respect to the aromatic ring by 11.2 (1) and 10.9 (1)°. All three hydroxy groups are involved in the formation of bifurcated intra- and intermolecular O—H...O hydrogen bonds. The crystal packing exhibits short O...O distances of 2.823 (2) Å between two O atoms of the nitro groups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In conclusion, the present investigation demonstrates again the high diversity of possible hydrogen-bonding interactions for polyamino-polyalcohols (PAPAs). Similar to our previous investigations into hydrogen bonding in the solid-state structures of free taci, taciÁHI and a cocrystal of these two components Reiß et al, 1999;Neis & Hegetschweiler, 2014), amine-alcohol interactions of the type R-O-HÁ Á ÁN(H 2 )-R constitute a predominant structural motif. The pairing mechanism of the vicinal amino-ethanol substructure may result in R 2 2 (10) ring formation, not only for the free ligand or its protonation products but also in the corresponding metal complexes.…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, the present investigation demonstrates again the high diversity of possible hydrogen-bonding interactions for polyamino-polyalcohols (PAPAs). Similar to our previous investigations into hydrogen bonding in the solid-state structures of free taci, taciÁHI and a cocrystal of these two components Reiß et al, 1999;Neis & Hegetschweiler, 2014), amine-alcohol interactions of the type R-O-HÁ Á ÁN(H 2 )-R constitute a predominant structural motif. The pairing mechanism of the vicinal amino-ethanol substructure may result in R 2 2 (10) ring formation, not only for the free ligand or its protonation products but also in the corresponding metal complexes.…”
Section: Tablesupporting
confidence: 88%
“…In terms of graph-set analysis (Bernstein et al, 1995), the resulting ten-membered ringpattern is represented by R 2 2 (10). It has recently been shown that the cyclic R 2 2 (10) motif is a predominant interaction type for taci molecules in solid-state structures (Neis & Hegetschweiler, 2014). However, in these previous investigations, the taci molecules or Htaci + cations were arranged in indefinite C 2 2 (12) chains, whereas in the Na and K complexes reported here, the basic R 2 2 (10) pattern is aligned as complex R 6 6 (30) and R 6 6 (42) rings ( Fig.…”
Section: Tablementioning
confidence: 99%